Food defense management plan implementation intention: an application of protection motivation theory - Yoon, Eunju (Kansas State University, 2007)
Protection motivation theory (PMT) was used in this study to investigate food service directors' food bioterrorism risk perception and their intentions to implement a food defense management plan in their operations. A cross sectional study using the self administered survey was conducted to test hypotheses. All measurement items for the construct of interests were assessed using a 7-point Likert type scales. Questionnaires were mailed in March 2007 to a national sample of 2,200 randomly selected on-site food service directors employed in school districts and healthcare operations. A total 449 usable completed questionnaires were received. Descriptive statistics were performed to investigate directors' perceptions, motivations and intentions independently. Before testing the actual hypotheses, confirmatory factor analysis was conducted to assess reliability and construct validity of the measurement model. Food service directors perceived that the result of a food terrorist attack would be severe but the chances it would occur in their operations is limited. They agreed that implementation of a food defense management plan would be effective to address food terrorism issue in their operations. They were highly motivated to protect the operation from an attack and to avoid the risk of terrorism and intended to implement a food defense plan in their operation. Based on the hypotheses testing, results revealed that motivation to protect the operation against food bioterrorism is higher when directors perceived a higher level of risk (severity and vulnerability), rated the effectiveness of a food defense management plan in protecting the operation high, and perceived that their operations were able to implement it. In turn, high level of motivation to protect the operation led to higher level of implementation intention. Results of the study can be used to design communication resources developed to enhance food service directors' intention to implement a food defense management plan. Educational and informational resources related to intentional food contamination and its defense should emphasize response efficacy and possibility perception.
Keywords: protection motivation theory; school food service operations; food service operations in health care; food terrorism; food terrorism risk perception; food defense management plan; Business Administration, Management (0454); Operations Research (0796)